The Effect of Intangible Assets, Research and Development Costs, and Modern Technology Investment on the Relationship between Profitability and Firm Value - Yulitasari; Syarifuddin Rasyid; Syamsuddin; Refor Moerdianto (Jurnal Ilmu Manajemen Profitability, 2025)
This study investigates the influence of profitability on firm value and further examines the moderating roles of intangible assets, research and development (R&D) expenditures, and technology investments in Indonesian manufacturing companies. The issue of how firms translate profitability into long-term value remains an important topic in financial and strategic management, particularly in emerging markets where resource allocation and investment strategies vary considerably. The research population comprises manufacturing firms listed on the Indonesia Stock Exchange during the period 2019–2023. Using purposive sampling, 105 firms were selected, resulting in 525 firm-year observations. Data were obtained from annual reports and financial statements, while the analytical methods employed include panel data regression, simple regression, and moderated regression analysis using EViews 12 software. The empirical results confirm that profitability exerts a positive and significant impact on firm value, highlighting its role as a primary driver of shareholder wealth. Nevertheless, the moderating tests indicate that intangible assets and technology investments weaken this relationship, suggesting that excessive or misaligned allocations in these areas may reduce the incremental benefits of profitability. Conversely, R&D expenditures were found not to significantly moderate the profitability–value link, implying that research activities alone do not automatically enhance firm value unless effectively commercialized. Overall, the findings enrich the literature on the resource-based view by emphasizing the conditional effects of intangible and technological resources. For practitioners, the study provides strategic insights into how managers should align resource investments with profitability objectives to optimize value creation in the manufacturing sector.